Effect of Doses of Clover Leaves Extract (Syzygium Aromaticum) on Death of Culex Sp Mosquito Larva - Ela Amelia; Aryl Alfath Muhamad Iqbal; Siti Fatimah; Kurnia Afrianti; Dhiny Isma (PT FORMOSA CENDEKIA GLOBAL, 2024)
The clove plant (Syzygium Aromaticum) is a medicinal plant that has various uses. One of its uses is as a biopesticide (larvicide). Clove leaves contain toxic substances for insects such as several chemical compounds eugenol, saponins, flavonoids and tannins.This research is an experiment, in terms of the aim of this research it is classified as verification research with the aim of determining the effect of clove leaf extract (Syzygium Aromaticum) dosage on the death of Culex Sp mosquito larvae. In this study, 5 containers were used, each container contained 10 larvae out of 150 larvae, 4 containers were given clove leaf extract at a dose of 5ml, 10ml, 15ml and 20ml in 1 container as a control (without treatment). The data obtained was tested using the Anova test.Data from statistical analysis research between 0 milli control (without treatment) with a calculated F value of 7.867 and this significant value is smaller than α=0.05, so the research hypothesis is accepted, meaning that with 3 repetitions with doses of 5ml, 10ml, 15ml and 20ml there is a significant effect in killing Culex Sp larvae. Clove Leaf Extract (Syzygum Aromaticum) can inhibit the growth of Culex Sp mosquito larvae.